Tausug & the Sulu Sultanate - Asreemoro, 1977-; Abu Bakar Ahmad (Kuala Lumpur : Saba Islamic Media, 2008)
History of the Tausug people and their role in Islamic civilization in Sulu Sultanate
Keywords: Sulu (Sultanate) -- History; Tausug (Philippine people) -- History; Islam -- Philippines -- Sulu -- History; Muslims -- Philippines -- Sulu -- History; Sulu (Philippines) -- Politics and government